Autonomic Computing and Communications Systems Third International ICST Conference, Autonomics 2009, Limassol, Cyprus, September 9-11, 2009, Revised Selected Papers - Vasilakos, Athanasius V.; Beraldi, Roberto; Friedman, Roy.; Mamei, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the thirs International ICST conference on Autonomic Computing and Communication Systems, Autonomics 2009, held in Cyprus Univesity of Technology, Limassol, Cyprus, in September 2009. The 11 revised full papers out of 26 submitted and hosted 5 invited talks, covering various aspects of autonomic computing including application, middelware, networking protocols and evaluation.
Autonomics 2009 -- A-OSGi: A Framework to Support the Construction of Autonomic OSGi-Based Applications -- A Network-Coding Based Event Diffusion Protocol for Wireless Mesh Networks -- Expressing Adaptivity and Context Awareness in the ASSISTANT Programming Model -- Experiences in Benchmarking of Autonomic Systems -- An Online Adaptive Model for Location Prediction -- MPM: Map Based Predictive Monitoring for Wireless Sensor Networks -- Integrating Autonomic Grid Components and Process-Driven Business Applications -- Using a Teleo-Reactive Programming Style to Develop Self-healing Applications -- Sensor Selection for IT Infrastructure Monitoring -- Context-Aware Self-optimization in Multiparty Converged Mobile Environments -- Context Discovery in Mobile Environments: A Particle Swarm Optimization Approach -- ABSS@AS 2009 Workshop -- Consequences of Social and Institutional Setups for Occurrence Reporting in Air Traffic Organizations -- Can Space Applications Benefit from Intelligent Agents? -- A Generic Agent Organisation Framework for Autonomic Systems -- Metareasoning and Social Evaluations in Cognitive Agents -- Experiments on the Acquisition of the Semantics and Grammatical Constructions Required for Communicating Propositional Logic Sentences -- An Autonomic Computing Architecture for Self-* Web Services.
Keywords: Computer science; Operating systems (Computers).; Computer network architectures; Computer Communication Networks; Information systems; Artificial intelligence; Information Systems; Computer Science; Computer Communication Networks; Computer Systems Organization and Communication Networks; Management of Computing and Information Systems; Performance and Reliability; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics).